Perlindungan Hukum terhadap Pengguna Jasa Pinjaman Online dalam Perspketif Hukum Perjanjian Pinjam Meminjam - Sistri Wahyuni; Yofiza Media; Harniwati Harniwati; Amanda Bherlyana Putri (Universitas Sumatera Barat, 2025)
This study aims to determine the Legal Protection for Online Loan Service Users in the Legal Perspective of Lending Agreements. This study uses a normative juridical analysis method by reviewing related laws and regulations and relevant legal literature. The results of the study indicate that in the (P2P) Lending scheme, the legal relationship occurs between the Lender and the Organizer, and between the Lender and the Borrower. The Lender authorizes the Organizer to distribute funds, while the main relationship is a loan agreement between the Lender and the Borrower. The legal relationship between the lender and the borrower is a loan agreement (debt) as regulated in Article 1754 of the Civil Code. The Lender acts as a creditor, and the Borrower acts as a debtor. Legal protection is needed to provide legal certainty for the Lender, especially in cases of default. Legal protection can be carried out preventively (before a dispute) by implementing basic principles of the organizer such as transparency, fair treatment, reliability, data confidentiality, and simple, fast, and affordable dispute resolution. Legal protection can also be provided repressively (after a dispute) through complaints and compensation if there is evidence of error or negligence by the provider. The Financial Services Authority (OJK) plays a crucial role in regulating and overseeing fintech P2P lending activities to protect the interests of lenders.